2002
DOI: 10.1001/jama.288.18.2271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cognitive Training Interventions With Older Adults

Abstract: Results support the effectiveness and durability of the cognitive training interventions in improving targeted cognitive abilities. Training effects were of a magnitude equivalent to the amount of decline expected in elderly persons without dementia over 7- to 14-year intervals. Because of minimal functional decline across all groups, longer follow-up is likely required to observe training effects on everyday function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

58
1,435
10
53

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,770 publications
(1,594 citation statements)
references
References 43 publications
58
1,435
10
53
Order By: Relevance
“…In individual studies (table 1), significant improvements were reported for cognitive training compared to no intervention in 19 of 26 memory outcome measures (Bailey et al, 2010;Bottiroli and Cavallini, 2009;Buiza et al, 2008;Cavallini et al, 2010;Cheng et al, 2012;Craik et al, 2007;Edwards et al, 2002;Fairchild and Scogin, 2010;Hastings and West, 2009;Jackson et al, 2012;Mahncke et al, 2006;Valentijn et al, 2005), in seven out of 16 measures of executive function (Ball et al, 2002;Buiza et al, 2008;Cheng et al, 2012;Craik et al, 2007;Edwards et al, 2002;Jackson et al, 2012;Mahncke et al, 2006;Margrett and Willis, 2006), and on both composite measures of cognitive function (Cheng et al, 2012;Mahncke et al, 2006). One trial found that reasoning training resulted in less self-reported decline in everyday functioning compared to control (Ball et al, 2002;Willis et al, 2006).…”
Section: Cognitive Training Versus 'No Intervention'mentioning
confidence: 99%
See 2 more Smart Citations
“…In individual studies (table 1), significant improvements were reported for cognitive training compared to no intervention in 19 of 26 memory outcome measures (Bailey et al, 2010;Bottiroli and Cavallini, 2009;Buiza et al, 2008;Cavallini et al, 2010;Cheng et al, 2012;Craik et al, 2007;Edwards et al, 2002;Fairchild and Scogin, 2010;Hastings and West, 2009;Jackson et al, 2012;Mahncke et al, 2006;Valentijn et al, 2005), in seven out of 16 measures of executive function (Ball et al, 2002;Buiza et al, 2008;Cheng et al, 2012;Craik et al, 2007;Edwards et al, 2002;Jackson et al, 2012;Mahncke et al, 2006;Margrett and Willis, 2006), and on both composite measures of cognitive function (Cheng et al, 2012;Mahncke et al, 2006). One trial found that reasoning training resulted in less self-reported decline in everyday functioning compared to control (Ball et al, 2002;Willis et al, 2006).…”
Section: Cognitive Training Versus 'No Intervention'mentioning
confidence: 99%
“…One trial found that reasoning training resulted in less self-reported decline in everyday functioning compared to control (Ball et al, 2002;Willis et al, 2006). For secondary outcomes, significant improvements were reported for training versus control in four out of six measures of subjective cognitive performance (Fairchild and Scogin, 2010;Hastings and West, 2009;Valentijn et al, 2005).…”
Section: Cognitive Training Versus 'No Intervention'mentioning
confidence: 99%
See 1 more Smart Citation
“…In the first of two reports by Willis and colleagues, Ball et al (2002) showed that each intervention led to immediate improvements in function on tasks specific to that cognitive domain. Further, these enhancements were maintained for over 2 years with booster interventions (Ball et al 2002). When individuals were followed across an additional 3 years (for a total of 5 years), those receiving reasoning training had less difficulty with activities of daily living, although the same effect was not seen in the memory or speed of processing training groups (Willis et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies report a link between cognitive stimulation and healthy brain aging; in systematic and controlled experiments using cognitive training interventions, significant long lasting cognitive improvements are observed (Yesavage 1985;Ball et al 2002; also see review by Acevedo and Loewenstein 2007). For example, in a series of studies by the ACTIVE (Advanced Cognitive Training for Independent and Vital Elderly) study group, older-independentliving adults were provided with one of four treatment conditions: three groups received ten training sessions either for memory, reasoning or speed of processing.…”
Section: Introductionmentioning
confidence: 99%